Penegakan Hukum terhadap Gerakan Ekstremisme yang Beredar di Indonesia Perspektif Fikih Jinayah: Studi Kasus FPI - Setyowati, Novita; Syaifuddin , Muhammad Irfan; Mardani , Nofi; Isnawati , Nurul (Al-Jinayah : Jurnal Hukum Pidana Islam, 2021)
This research was conducted to analyze cases that occured with the FPI object, in order to get a bright spot on law enforcement. The murder case of 6 members of the FPI group is still in the process of being investigated, so there are several possibilities for law enforcement that might apply. Prior to this case, FPI was also often involved in extreme anarchist acts, and the people who saw it would call it aradical group. Based on a series of cases that occurred which of course involved FPI with residents, the community, and security forces. There are 3 possible articles of law enforcement in Indonesia that will apply according to UU, namely article 383 of the Criminal Code regarding accidental disappearances, and Article 340 of the Criminal Code regarding premeditated murder, as well as Article 170 of the Criminal Code regarding acts of violence. The perspective that the writer will aim at is the perspective of Jinayah Jurisprudence. So, if the law enforcement is brought to the realm of the jinayah, there are also several kinds of choices of law, namely qis}a>s} if it is proven to kill deliberately and deliberately. The next choices of law is to pay diyah if it is accidental, and also kaffarah, namely relief from Diyat.